The EU convergence machine at work. To the benefit of the EU's poorest citizens? - Goedemé, T; Collado, D (Wiley, 2016)
Social cohesion in the EU (European Union) is usually assessed on the basis of GDP per capita and relative poverty rates. These indicators show that the ‘European convergence machine’ led to greater social cohesion between old and new Member States (EU‐15 and NMS) until the onset of the crisis. In this article we offer an alternative perspective by directly comparing EU citizens’ disposable household incomes. Using four waves of EU‐SILC data, we explore what happened between 2005 and 2011 in the EU‐15 and NMS regarding changes in the lowest household incomes in relation to the EU‐wide median. Results show that, overall, the convergence machine seemed to work well for the lowest incomes in the NMS, but not so much for those living in the EU‐15. At the same time, differences in living standards remain quite large. This points to important continued challenges for EU policy initiatives in the social domain.